International tourism and urban transformation in Old Havana - Völkening, Niklas; Benz, Andreas; Schmidt, Matthias (ERDKUNDE, 2019)
Cuba is currently experiencing an unprecedented boom in international tourism, and the Cuban state has actively supported tourism expansion as a strategic means to increase greatly needed foreign currency income, in order to sustain its socialist system. In Havana, Cuba’s gateway city for international tourists and – with its colonial old town bestowed with UNESCO world heritage status – one of its touristic hotspots, this tourism boom is felt most profoundly. The old town has been subject to far-reaching processes of urban restructuring, driven by state-run urban renewal projects, thereby increasing touristic influx and the gradual displacement of dwellers and resident-oriented urban functions by tourism-oriented ventures. This article provides an analysis of the recent spatio-structural urban transformation processes in Habana Vieja, highlighting particularly its interrelations with international tourism, the role of the Cuban government as a major tourism facilitator and the state-run old town restoration programme. Our analysis shows that in the context of old town restructuring in Havana, the Cuban government often favours touristic needs over those of local dwellers, albeit some of them may indeed profit from increasing touristification. Meanwhile, the government is willing to accept, at least in controlled settings, market-based developments otherwise strongly opposed by official state ideology.